Effects of consecutive days of resistance exercise on the immune system - Ng, Daniel Chin Chuan (2014)
Exercise induces physiological changes to the immune system. Effects of resistance exercise (RE) on the immune system, and the temporal changes in immune response over a bout of 3 consecutive days of RE have not been extensively explored. This study examines the relationship between RE and the immune system, particularly on 4 immune markers (IM): White blood cells (WBC), lymphocytes, monocytes and platelets. Ten healthy, resistance-trained males performed 3 set of 10 repetitions of 5 REs at their 10 repetition max (RM) for 3 consecutive days. Antecubital venous blood samples were collected at pre-, post-RE trial each day, as well as 23 hours post day 3 of RE trials. ANOVA – Significant interaction was found in monocytes count, at pre-RE and post-RE for day 1 and day 2 of RE trials. Main effect of time was significant in all 4 IM counts. Paired t-test – Baseline levels of lymphocytes and platelets count (PLC) during pre-RE trial and 23 hours post day 3 of RE were significantly different. Cortisol response and apoptosis could contribute to decrease in lymphocytes and monocytes count, resulting in overall decrease in WBC count, while RE-induced epinephrine, sheer stress and hemoconcentration could result in the decrease in PLC of participants each day. Sustained decreased level of lymphocytes and PLC 23 hours after RE trials could indicate the onset of infection due to consecutive days of RE. In conclusion, RE induces significant temporal changes to the immune system. Engaging in 3 consecutive days of RE may weaken the immune system.